Physiological, Nutritional and Metabolomic Responses of Tomato Plants After the Foliar Application of Amino Acids Aspartic Acid, Glutamic Acid and Alanine - Alfosea-Simón, Marina; Simón-Grao, Silvia; Zavala-Gonzalez, Ernesto Alejandro; Cámara-Zapata, Jose Maria; Simón, Inmaculada; Martínez-Nicolás, Juan José; Lidón, Vicente; García-Sánchez, Francisco (Frontiers in Plant Science, 2021)
Agriculture is facing a great number of different pressures due to the increase in population and the greater amount of food it demands, the environmental impact due to the excessive use of conventional fertilizers, and climate change, which subjects the crops to extreme environmental conditions. One of the solutions to these problems could be the use of biostimulant products that are rich in amino acids (AAs), which substitute and/or complement conventional fertilizers and help plants adapt to climate change. To formulate these products, it is first necessary to understand the role of the application of AAs (individually or as a mixture) in the physiological and metabolic processes of crops. For this, research was conducted to assess the effects of the application of different amino acids (Aspartic acid (Asp), Glutamic acid (Glu), L-Alanine (Ala) and their mixtures Asp+Glu and Asp+Glu+Ala on tomato seedlings (Solanum lycopersicum L.). To understand the effect of these treatments, morphological, physiological, ionomic and metabolomic studies were performed. The results showed that the application of Asp+Glu increased the growth of the plants, while those plants that received Ala had a decreased dry biomass of the shoots. The greatest increase in the growth of the plants with Asp+Glu was related with the increase in the net CO2 assimilation, the increase of proline, isoleucine and glucose with respect to the rest of the treatments. These data allow us to conclude that there is a synergistic effect between Aspartic acid and Glutamic acid, and the amino acid Alanine produces phytotoxicity when applied at 15mM. The application of this amino acid altered the synthesis of proline and the pentose-phosphate route, and increased GABA and trigonelline.